Bringing the state back in: India's 2015 model BIT - Srividya Jandhyala (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
India's new model BIT reflects a shift toward governing the conduct of foreign investors, and away from mere protection. The author considers how changes in the 2015 Model serve to reinforce the role of the state, and notes key challenges that may arise in practice.
Keywords: 330